Model Matematika untuk Memprediksi Volume Telur Itik Alabio - Nursyam Andi Syarifuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to predict the egg volume of Alabio ducks based on the Westerskov (1950) model by finding the volume coefficient (Kv) based on the length and width of the eggs and validating the accuracy of the model obtained with the actual volume. This study uses a quantitative observation method based on the Westerskov model (1950) with the equation: V = Kv×P×L2, to predict volume in duck eggs Alabio. This study was divided into two stages, namely the first stage of Model Development using 350 Alabio duck eggs to find the Kv value by dividing the actual volume value of the eggs by the product of the length and width of the eggs that have been measured. The second stage is Model Validation using 150 eggs to validate the formula obtained in the first stage. The Kv value obtained in the first stage was applied to estimate the volume of 150 eggs using the Westerskov (1950) model. The predicted volume value of the 150 eggs obtained is then compared with the actual volume of the 150 eggs. The model obtained was then validated with the values of Mean Bias, Modeling Efficiency (MEF), Root Mean Squared Error of Prediction (RMSEP), and Concordance Correlation Coefficient (CCC). Based on the analysis results, the Kv value obtained to predict the egg volume of Alabio ducks is 0.48, so the mathematical model is ???? = 0.48×P×L2. The validation results show that the model is feasible to use (MEF=0.68) with a high level of accuracy (CCC=0.84).